1996
DOI: 10.1002/jbmr.5650111204
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a polymorphism at the translation initiation site of the vitamin D receptor gene is associated with low bone mineral density in postmenopausal mexican-American women

Abstract: We examined the association of bone mineral density (BMD) with a polymorphism in the gene encoding the vitamin D receptor (VDR) that causes a change in the predicted protein sequence. The polymorphism results from a C-to-T transition and creates an initiation codon (ATG) three codons proximal to a downstream start site. The polymorphism can be defined by a restriction fragment length polymorphism (RFLP) using the restriction endonuclease FokI. The presence of a FokI site, designated f, allows protein translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(110 citation statements)
references
References 14 publications
4
99
0
7
Order By: Relevance
“…(11,24) Based on these findings, we cloned and sequenced the patient's individual cDNAs representing the two FokI (f/F) polymorphic alleles in order to further demonstrate that the patient had only a single heterozygous mutation in the VDR gene and to rule out the presence of an additional mutation. Sequencing showed that the E420A mutation was present on the f/M1 allele and therefore was inherited from the father.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11,24) Based on these findings, we cloned and sequenced the patient's individual cDNAs representing the two FokI (f/F) polymorphic alleles in order to further demonstrate that the patient had only a single heterozygous mutation in the VDR gene and to rule out the presence of an additional mutation. Sequencing showed that the E420A mutation was present on the f/M1 allele and therefore was inherited from the father.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing also showed that the patient and her father were heterozygous for the FokI polymorphism (F/f) located in the translation initiation start site (data not shown). (11,24) To further demonstrate that the patient had only a single heterozygous mutation in the VDR gene, we cloned and sequenced the VDR cDNAs that were generated from the two different F/f site alleles. The cDNA sequence from the patient's f site allele had the E420A mutation, like the father, whereas the cDNA sequence from the F site allele was completely normal, like the mother.…”
Section: Mutational Analysesmentioning
confidence: 99%
“…Similarly, Colin et al (2000) showed a significantly lower (50%) effective dose of 1,25-(OH) 2 D 3 in the FokI C/C genotype than in FokI C/T genotype. By switching from ATG (FokI T) to ACG (FokI C) polymorphism, the first potential start site moves to the 3 0 direction, resulting in proteins that are three amino acids shorter and more functional (Gross et al, 1996). Thus, patients with FokI C/C may react more to vitamin D, resulting in a higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Gross et al [15] conducted a study in postmenopausal Mexican-American women, showed that FokI polymorphism of the VDR gene correlates significantly with decreased BMD at the lumbar spine and an increased rate of bone loss at the hip in ff subjects. In another study of postmenopausal Italian women population, Gennari L [16] observed a weak association between FokI polymorphism and lumbar BMD (p = 0.06) but no reveland to femoral neck BMD(p = 0.5).…”
Section: Introductionmentioning
confidence: 99%